Supplier Selection for Supply Chain by Risk-Averse Decision Maker with Multi-Criteria Decision Making - Ghasemi, Fatemeh; Khadem, Mehdi; Pourghader Chobar, Adel (International journal of industrial engineering and operational research, 2023)
Supplier selection is a critical decision in supply chain management, as it can have a significant impact on the performance of the entire supply chain. Risk-averse decision makers are particularly concerned about the risks associated with supplier selection, such as supplier failure, quality problems, and delivery delays. Multi-criteria decision making (MCDM) is a powerful tool that can be used to support supplier selection decisions by considering multiple criteria simultaneously. In this paper, we propose a new MCDM-based supplier selection model for risk-averse decision makers. The model takes into account both quantitative and qualitative criteria, such as price, quality, delivery, lead time, financial stability, and reputation. The model also considers the risk of each supplier, which is assessed using a variety of factors, such as the supplier's past performance, financial health, and industry outlook. The proposed model is applied to a real-world case study of a manufacturing company. The results show that the model can be used to select suppliers that meet the company's requirements and minimize the risk of supply disruptions.